MICROPROPAGATION JILIN SMALL GRANULE SOY TRANSFERRED GmMYB12A - Van Phong, Nguyen; Thi Thu Huong, Bui; Wang, QingYu (Journal of Forestry Science and Technology, 2019)
The isoflavones of soybean, is a class of secondary metabolite, which affects cell division, new cell formation, and may enhance the nutritional value and thus guarantee better health. The soybean transferred the GmMYB12A gene, containing high levels of isoflavones, which could improve the valuable soybean productivity, thus, the significant micropropagation was studied. The result revealed that the half-seed method, with proper disinfection time for Jilin small granule soy was used in 15 hours with chlorine gas produced by pouring 100 ml of 4% sodium hypochlorite into a beaker and adding 4 ml of 12 N hydrochloric acid. In vitro regeneration of Jilin small granule soy was succeeded through multiplication axillary buds from half-seed soybean by using appropriate levels of some growth regulators supplemented in regeneration mediums such as B5 + 2 ml/L BAP for shoot multiplying; MS + 5 μg/L TRIA+ 1mg/L Zeatin + 0.5 mg/L GA3 + 0.1 mg/L IAA for shoot elongation and 1/2 MS + 1.25 mg/L IBA or 1/2 MS + 1.1 mg/L IAA for rooting. The report also determined the appropriate substrate as 1 the soil: 1 humus: 1 sawdust ratios for plantlets to grow in a greenhouse.